The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1977
DOI: 10.1136/ard.36.1.80
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre trial of naproxen and phenylbutazone in acute gout.

Abstract: SUMMARY Naproxen 750 mg as a single dose followed by 250 mg three times daily has been compared with phenylbutazone 200 mg four times daily for 48 hours followed by 200 mg three times daily for the treatment of acute gout in an open study on 41 patients.The drugs were equally effective with few and relatively mild side effects. Naproxen is a useful alternative agent for the treatment of acute gout.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 18 publications
1
15
0
2
Order By: Relevance
“…Few comparative studies of non-steroidal antiinflammatory drugs have been undertaken in acute gout, but indomethacin (Smyth & Percy, 1973), naproxen (Sturge et al, 1977) and feprazone (Reardon et al, 1980) appear to be of similar efficacy to phenylbutazone, with a mean interval of approximately 4 days between the onset of treatment and resolution of the attack: an interval similar to that seen in the present study. Fenoprofen (Weiner et al, 1979) and ketoprofen (Siegmeth & Placheta, 1976) were also considered to be of similar efficacy to phenylbutazone, but the data did not include the duration of attack following initiation treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Few comparative studies of non-steroidal antiinflammatory drugs have been undertaken in acute gout, but indomethacin (Smyth & Percy, 1973), naproxen (Sturge et al, 1977) and feprazone (Reardon et al, 1980) appear to be of similar efficacy to phenylbutazone, with a mean interval of approximately 4 days between the onset of treatment and resolution of the attack: an interval similar to that seen in the present study. Fenoprofen (Weiner et al, 1979) and ketoprofen (Siegmeth & Placheta, 1976) were also considered to be of similar efficacy to phenylbutazone, but the data did not include the duration of attack following initiation treatment.…”
Section: Discussionsupporting
confidence: 74%
“…The FDA has approved naproxen (Evidence A) (33, 34), indomethacin (Evidence A) (26, 27, 31, 32), and sulindac (Evidence B) (35) for the treatment of acute gout. However, analgesic and anti-inflammatory doses of other NSAIDs may be as effective (Evidence B–C).…”
Section: Resultsmentioning
confidence: 99%
“…Although only a few open-label studies have reported quantitative results, nearly all have concluded clinical benefit associated with short-term NSAID therapy. Controlled studies have employed comparator groups that have included indomethacin [34][35][36][37], phenylbutazone [38][39][40][41][42][43], or a different dose of the study drug [44,45]. Although generally deemed beneficial with good tolerability, there have been no substantial differences between the study agents and comparator drugs.…”
Section: Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%